Teaching English Using Flashcards to Improve Elementary School Students’ Vocabulary - Farrah Aufa Khasani Putri; Maryam Sorohiti; Teguh Ariebowo (Universitas Muhammadiyah Yogyakarta, 2023)
Acquiring new English words is a challenge for students because they commonly need to learn to use the words in their daily lives, which are dominated by their first language for communication. Flashcards are instrumental in facilitating their vocabulary learning. This research examined flashcards' use in teaching and learning English language vocabulary. This research used a quantitative approach with an experimental design. The data was collected by asking students to do a vocabulary test before and after the treatment. The object of this research was fourth-grade students in a private primary school in Yogyakarta, Indonesia. The results indicated that the student's English vocabulary level on the pre-test was at the intermediate level, which showed a mean score of 52.20. Meanwhile, on the post-test, the student's English vocabulary level was at an advanced level, showing a mean score of 77.60. In addition, the Wilcoxon test showed that the p-value of asymp.sig.2tailed was 001. It means that the students’ English vocabulary significantly improved after being taught using flashcards. It indicates that the hypothesis that flashcards have significantly improved students' vocabulary was accepted.